2015
DOI: 10.1111/rec.12273
|View full text |Cite
|
Sign up to set email alerts
|

The effects of riparian restoration following saltcedar (Tamarix spp.) biocontrol on habitat and herpetofauna along a desert stream

Abstract: Amphibians and reptiles (herpetofauna) have been linked to specific microhabitat characteristics, microclimates, and water resources in riparian forests. Our objective was to relate variation in herpetofauna abundance to changes in habitat caused by a beetle used for Tamarix biocontrol (Diorhabda carinulata; Coleoptera: Chrysomelidae) and riparian restoration. During 2013 and 2014, we measured vegetation and monitored herpetofauna via trapping and visual encounter surveys (VES) at locations affected by biocont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 42 publications
(61 reference statements)
0
7
0
3
Order By: Relevance
“…On the Lower Virgin River habitat structure was altered by defoliation in monotypic tamarisk stands. Amount of bare ground increased from 9–10% during predefoliation (Bateman & Ostoja ), to 23% during postdefoliation conditions (Mosher & Bateman ). Canopy cover was reduced from 82% predefoliation to 72% postdefoliation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…On the Lower Virgin River habitat structure was altered by defoliation in monotypic tamarisk stands. Amount of bare ground increased from 9–10% during predefoliation (Bateman & Ostoja ), to 23% during postdefoliation conditions (Mosher & Bateman ). Canopy cover was reduced from 82% predefoliation to 72% postdefoliation.…”
Section: Discussionmentioning
confidence: 99%
“…Sites on the Lower, Middle, and Upper Dolores River, the Colorado River near Moab, the San Juan River, and tributary streams have been monitored through annual summer field surveys since 2008 (van Riper unpublished data; Jamison et al ; Nagler et al ). Sites on the Virgin River have been monitored since 2009 (Bateman et al ; Bateman & Ostoja ; Nagler et al ; Mosher & Bateman ). Other sites have been surveyed from 2007–2015 by the Tamarisk Coalition and reported in presence‐absence maps (Tamarisk Coalition ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We measured habitat where we found gartersnakes through tracking and visual observations. Fourth-order habitat measurements included vegetative, environmental, and hydrologic characteristics ( Table 1 ) recorded at each snake point, in a 1-m-diameter plot, and along four 2.5-m transects sensu [ 10 , 39 , 55 , 56 ] ( Fig 2 ). At each snake point, we measured aspect and slope, water depth, distance to water, and canopy cover (>1m in height).…”
Section: Methodsmentioning
confidence: 99%
“…Bullfrogs are well‐known invaders in the region and have been established for decades (Clarkson & DeVos, 1986), and their role as predators (Jennings & Hayes, 1994; Moyle, 1973), disease vectors (Schlaepfer, Sredl, Rosen, & Ryan, 2007), and competitors with local fauna (Bradford, Jaeger, & Shanahan, 2005) are recognized. Although bullfrogs dominated studies considering introduced species, other invasive taxa were also reported in the literature, including fish (Hossack et al, 2017; Maret et al, 2006; Reaser, 2001; Schalk, Montaña, Kralman, & Leavitt, 2018), crayfish (Witte, Sredl, Kane, & Hungerford, 2008), and plants (Mosher & Bateman, 2016; Tazik & Martin, 2002).…”
Section: Discussionmentioning
confidence: 99%